Description of students Mathematical anxiety based on the students’ mathematics ability - Rismayana; Dinar, Muh.; Minggi, Ilham (ARRUS Journal of Mathematics and Applied Science, 2021)
This study aims to see how the descriptions of anxiety student data are viewed from the level of students' mathematical abilities and is there a relationship between students 'math anxiety and the level of students' math abilities. This type of research uses quantitative methods to determine whether there is a relationship between students 'math anxiety and the level of students' mathematical abilities and qualitative methods to describe the characteristics of mathematics learning anxiety in terms of students' mathematical abilities. The subjects of this study were 3 students, namely one student with low math ability, one student with moderate math ability, and one student with high math ability. The research instrument consisted of a math ability test, an anxiety questionnaire and an interview guide. The level of math ability is categorized using standard deviation. The results showed that: In general, there is no relationship between students 'math anxiety level and students' math abilities in class XI IPA 2, however, some special cases show that there are children who have math anxiety in each category of math ability level (1) Students with low math abilities always experience symptoms of math anxiety because of low self-confidence, poor mastery of mathematical concepts, negative attitudes towards mathematics and passive (2) Students with moderate math abilities often experience math anxiety due to a high fear of mistakes, lack of mastery of mathematical concepts, perception of mathematics is difficult, and passive (3) Students with mathematical abilities rarely experience mathematics because the anxiety they experience is something that everyone naturally feels.